Growth, dry matter production and productivity of soybean grown under four solar radiation levels - Melges, Elena; Lopes, Nei F.; Oliva, Marco A. (Pesquisa Agropecuaria Brasileira, 2014)
Growth, dry matter production and productivity of soybean (Glycine max (L.) Merril), grown under field conditions al four light levels (30%, 50%, 70% and 100% of sunlight) were studied. Soybean growth presented three distinct phases: initial phase, from germination to flowering, in which growth was relatively slow, intermediate phase, between flowering and beginning of seed filling, when growth was accelerated; and, phase of seed development, when growth was very slow, with tendency of reaching a plateau. Shading reduced dry matter accumulation in the whole plant and its organs. Maximum dry weight productions of the organs were reached at the 92nd day for the leaves, at the 104th day for the roots, independently of light levels, at the 103rd day under half to full sunlight, and at the 108th day after emergence at 30% and 70% of sunlight for stens. There was a ten to fifteen-day difference between maximum stem and leaf growth. The dry matter accumulated in pericarps and seeds increased strongly until to final harvest in the highest light levels and slowly in the lowest light levels. There was a straight linear correlation (R² = 0.97) between yield and biomass. Shading extended the period of dry matter accumulation to all organs, meanly the maturation time. Solar radiation reduction increased shoot/root ratio, plant lodging and flower and pod drops. The harvest index was not modified by light levels.